Distribution of South American manatees, Trichechus manatus Linnaeus, 1758 and T. inunguis (Natterer, 1883) (Sirenia: Trichechidae) - Bonvicino, Cibele Rodrigues; Viana, Maria Carolina; Oliveira, Edivaldo H. C. de; Emin, Renata; Silva Junior, José de Sousa e; Sousa, Maura Elisabeth Moraes de; Siciliano, Salvatore (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
South America is unique as it is home of two species of manatees: the West Indian manatee, Trichechus manatus, and the Amazonian manatee, T. inunguis. These species are easily identified by the belly skin coloration, the first is entirely gray whereas T. inunguis has a white mark pattern in the belly, and presence of nails in T. manatus, absent in T. inunguis. The morphology and the range of Trichechus species have been clearly established. However, we show that the belly skin coloration and the presence of nails on the pectoral flipper may be polymorphic. These findings prompted us to check all available information about the manatee. In view of lack of accurate data on manatee locations, we produced a gazetteer and a map of Trichechus spp. in South America using records obtained by regular monitoring of aquatic mammal strandings conducted by the Grupo de Estudos de Mamíferos Aquáticos da Amazônia of the Museu Paraense Emílio Goeldi, all available peer-reviewed data, reports, thesis, and newspaper files with photos showing diagnostic characters. These findings showed the need of improving the identification of these species before implementing conservation strategies. Finally, we present a complete report on the extant distribution of these species in South America.
Keywords: Amazonas river basin; Amazonian manatee; Aquatic mammals; Atlantic Ocean; Conservation; West Indian manatee